Eficácia dos flavonóides hesperidina e naringenina e o fenol ácido isovanílico complexados com Mg (II), para o controle da bactéria xanthomonas citri ssp. citri - Silva, Danielle Fernandes da (Universidade Federal de São Carlos, 2017)
The present work describes the study of natural products complexed as bactericidal, bacteriostatic and biofilm inhibitors for the control of citrus canker, as well as their study regarding the mode of action of these complexes against citrus plants. Citrus canker is one of the main diseases of citriculture, where its etiological agent is a gram-negative bacterium, Xanthomonas citri ssp citri. For the control of this disease is used chemicals derived from copper, but some isolates of this bacterium already have resistance. The use of pesticides in world agriculture is of concern to the safety of the environment and human health. In this work, the hesperidin, naringenin and isovanilic acid complexes with metal magnesium ion (Mg) were prepared and characterized, and microbiological tests were performed with the complexes evaluating their Minimum Inhibitory Concentration (MIC), their Minimum Bactericidal Concentration (MBC) and Minimum Inhibitory Concentration of Biofilm at 50% (CIMB50) obtaining results such as CIM and CBM of 50 and 50 μg.mL-1 for the hesperidin complex; 12.5 and 50 μg.mL-1 for the naringenin complex and 6.25 and 6.25 μg.mL -1 for the isovanil complex, respectively. The free flavonoids and phenol presented MIC and MBC results equal to or greater than 400 μg.mL-1. Through studies of the activity of the complexes in microbial inhibition assays in citrus seedlings, it was possible to observe the control of the phytopathogen. The mechanism of action of the complexes in the plants was investigated by epifluorescence images being possible to visualize the compounds in the mesophyll of the leaves. The quantification of products complexed by HPLC-UV in the growth medium of the citrus seedlings allowed to confirm the proposal of action of the complexes via systemic action being strongly absorbed by the root.
Effectiveness of flavonoids hesperidine and naringenin and isovanyl acid phenol complexed with Mg (II), for the control of bacteria xanthomonas citri ssp. citri
Keywords: Flavonóides complexados; Bactéria; Xanthomonas; Inibição; Biofilme; Bactericida; Sistêmico; HPLC; Complexed flavonoids; Bacterium; Sistemic; Bactericide; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA